Partisipasi Masyarakat Lokal Dalam Pengembangan Pariwisata Di Kawasan Pariwisata Prioritas Pembangunan Pemerintah Provinsi NTT Tahun 2019 - Elim, Yuan Valentino; Mba, Deni Alfian (JURNAL DESTINASI PARIWISATA, 2021)
The Tourism Sector was chosen as the primemover of economic development in East Nusa Tenggara Province. One of the problems encountered in tourism development efforts in East Nusa Tenggara Province is related to the low participation of local communities. This study aims to (1) Explain the form and the level of participation of local communities and (2) Explain the obstacles / barriers faced by local communities in the development of tourism in the six priority development locations of the NTT provincial government in 2019. The type of this research is qualitative research. The data collection techniques used are in-depth interviews, observations, and library studies. Determination of the informants in this study is using snowball sampling. The results of the study indicate that the forms of local community participation consist from participation in activities directly related to tourism activities and participation in activities not directly related to tourism activities. Meanwhile, in terms of the level of participation, based on the concept of ladder of participation, the level of participation of local people in the six locations of this study is on the second ladder namely tokenism where local people are given the opportunity, invited to participate in the tourism sector but on the other hand they are not equipped with the ability adequate in the form of knowledge and skills as well as adequate infrastructure. As for the obstacles faced by local communities in participating in the tourism sector are (1) Lack of knowledge and skills to manage the potential of their resources; (2) There is no holistic, integrative and thematic and sustainable training concept, (3) Does not yet have a tourism activist in the village and a role model / pilot project location that has succeeded in developing the tourism sector as an example, (4) Apathy towards the program programs related to tourism development, (5) unfavorable infrastructure conditions, and (6) Lack of cooperation between local governments, non-governmental organizations engaged in the tourism sector and local communities. Keywords: participation, ladder of participation, community-based tourism